Welfare Impact of Improved Boat Modernisation Schemes (IBMS) in Pemalang Regency, Central Java, Indonesia - Susilowati, Indah (1991)
The overall objective of this study is to examine the welfare impact of the IBMS programme in Pemalang Regency Central Java, Indonesia. To achieve this objective, supply and demand models for fish were estimated . The simultaneous equation model consists of supply,demand,and identity equations. The Two Stage Least Square (2 SLS) was utilized to estimate the model using time series quarterly data from 1976.2 to 1990.2. All the key variables in the model were found to be consistent with postulated behaviour and theoretical expectations. All variables specified in the supply model had expected signs and significant except for the fishing effort and the probability to catch fish. As expected the supply function was found to be positively related with respect to its own price. However, its price elasticity in pre-IBMS is greater (0.224) than in post-IBMS (0.126). This shows that the rate of increase in fish product ion from additional input is diminishing after IBMS as evidence to the existence of over exploitation of the resource in the study area. All of the signs of estimated parameters in the demand model were consistent with the theory except for the lagged price of fish variable. Results also showed that all of coefficient parameters were greater than half of their standard errors except for the intercept and lagged quantity demand at pre-ISMS. Furthermore, the price of substitute goods and income were found to be the major determinants of the quantity of fish demanded. The elasticity of fish demanded with respect to its own price i s greater (-0.676) at post-ISMS than a t pre-ISMS (-0.295). However, the income elasticity of demand for fish was found to be more elastic before (0.740) than after(0.580) IBMS. The welfare analysis showed that the IBMS programme was ineffective. The overall impact showed that welfare loss to the society was 142.86 percent from the original condition. The biggest loss (two-third) was incurred by consumer sand the remainder was incurred by producers.